2018
DOI: 10.1155/2018/2154893
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Characterization,In VitroAntioxidant Activity, and Quantitative Analysis by Micellar Electrokinetic Chromatography of Hawthorn (Crataegus pubescens) Fruit

Abstract: Due to their antioxidant properties, polyphenolic compounds are considered beneficial for human health. In this work, we investigated the polyphenol profile and antioxidant activity of edible tejocote (Crataegus pubescens) fruit extracts by micellar electrokinetic chromatography (MEKC) and HPLC/UV. The major phenolic compounds in the pulp extracts were (+)-catechin (9.17 ± 0.20 mg/100 mg dry fruit), (−)-epicatechin (4.32 ± 0.11 mg/100 mg dry fruit), and chlorogenic acid (5.60 ± 0.24 mg/100 mg dry fruit). The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…is a fruit that grows naturally in Turkey, belonging to the Rosaceae maloidea sub-family (Dönmez, 2004). It is mainly grown in northern regions of East Asia, Europe, and North America (González-Jiménez et al, 2018). Hawthorn which generally has thorns grows mainly on limestone soils, wooded and sunny areas up to 1500 m above sea level.…”
Section: Evaluation Of Physicochemical Characteristics Antioxidant Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“…is a fruit that grows naturally in Turkey, belonging to the Rosaceae maloidea sub-family (Dönmez, 2004). It is mainly grown in northern regions of East Asia, Europe, and North America (González-Jiménez et al, 2018). Hawthorn which generally has thorns grows mainly on limestone soils, wooded and sunny areas up to 1500 m above sea level.…”
Section: Evaluation Of Physicochemical Characteristics Antioxidant Ac...mentioning
confidence: 99%
“…Swaminathan et al (2010), reported a cardioprotective and antiradical effect of phenolic extracts from Crataegus oxycantha fruits. González-Jiménez et al (2018), study investigating the polyphenol profile and antioxidant content of fruit extracts reported that hawthorn has excellent potential as a natural source of antioxidant phenolic compounds and can be used as a nutraceutical and functional food.…”
Section: Evaluation Of Physicochemical Characteristics Antioxidant Ac...mentioning
confidence: 99%
“…The consumption of colorful and native species increases day by day thanks to beneficial effects on health. Hawthorn is one of these species that contain high amounts of bioactive compounds such as organic acid, sugars, antioxidants, phenolic constituents, and vitamin C (Edwards et al, 2012;Gonzalez-Jimenez et al 2018;Alirezalu et al, 2018;Muradoğlu et al, 2019). Its fruits are rich in vitamins, carbohydrates, and sugar.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the chemical composition of Mexican Crataegus species, chlorogenic acid, (+)-catechin, (-)-catechin, quercetin, kaempferol and apigenin glycosides have been identified in the ethanolic extracts obtained from the fruits of C. stipulosa , C. mexicana , C. nelsoni ( García-Mateos et al, 2013 ) and C. pubescens ( González-Jiménez et al, 2018 ) . Additionally, ursolic, corosolic and euscapic acids have been identified in the methanolic extracts obtained from the leaves and flowers of C. gracilior ( Hernández-Pérez et al, 2014 , Torres-Ortiz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%